The phenomenon of multiple wordformation motivation in linguistics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the multiple wordformation motivation in linguistics, its specificity in the Ukrainian language. Polymotivation – the result of historical development of a word (group of words). The basic kinds of multiple motivation in the Ukrainian language after Z.S.Kaspryshyn are allocated.
Keywords: wordformation motivation; derivative; polymotivation